2023
DOI: 10.3390/ijms241210047
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptome Sequencing and WGCNA Reveal Key Genes in Response to Leaf Blight in Poplar

Abstract: Leaf blight is a fungal disease that mainly affects the growth and development of leaves in plants. To investigate the molecular mechanisms of leaf blight defense in poplar, we performed RNA-Seq and enzyme activity assays on the Populus simonii × Populus nigra leaves inoculated with Alternaria alternate fungus. Through weighted gene co-expression network analysis (WGCNA), we obtained co-expression gene modules significantly associated with SOD and POD activities, containing 183 and 275 genes, respectively. We … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 55 publications
0
2
0
Order By: Relevance
“…This analysis helps us identify candidate genes closely associated with our research (Langfelder and Horvath, 2008). Using WGCNA, 15 TFs related to poplar leaf blight, including ATWRKY75, ANAC062, ATMYB23 and ATEBP, were identified, and these TFs exhibited high connectivity in the network (Wang et al, 2023). In potatoes, WGCNA identified 40 key candidate genes associated with development (Wei et al, 2023).…”
Section: Discussionmentioning
confidence: 99%
“…This analysis helps us identify candidate genes closely associated with our research (Langfelder and Horvath, 2008). Using WGCNA, 15 TFs related to poplar leaf blight, including ATWRKY75, ANAC062, ATMYB23 and ATEBP, were identified, and these TFs exhibited high connectivity in the network (Wang et al, 2023). In potatoes, WGCNA identified 40 key candidate genes associated with development (Wei et al, 2023).…”
Section: Discussionmentioning
confidence: 99%
“…Ruiqi Wang identified four transcription factors related to disease resistance, including AtWRKY75, ANAC062, AtMYB23 and AtEBP, through the leaves of poplar (P. simonii × P. nigra) [39]. Further studies have shown that PsnWRKY70 enhances poplar resistance to Rhizoctonia allochthonii by activating genes related to pathogen-related molecular patterns (PTI) and effector-induced immunity (ETI) [40].…”
Section: Research Progress Of P Simonii Genomicsmentioning
confidence: 99%